Control of Malolactic Fermentation in Wine. A Review - Bauer, R.; Dicks, L.M.T. (South African Journal of Enology and Viticulture, 2017)
Malolactic fermentation (MLF) is conducted by lactic acid bacteria (LAB) and refers to the decarboxylation of Lmalate to L-lactate. This secondary fermentation is difficult to control and is mainly driven by Oenococcus oeni.  Uncontrolled MLF, especially in wines with a high pH, which are typical of warmer viticultural regions, may render the wine unpalatable or even cause spoilage. In this review we focus on wine compounds and emphasise factors that affect the growth of 0. oeni and MLF, and discuss practical applications.  We also explore alternative technologies that may enable better control over MLF.